Formação permanente de professores de língua portuguesa e o ensino de produção textual, no contexto da educação básica, técnica e tecnológica - Teixeira, Betina Waihrich Marim (2017)
The work entitled "Permanent Training of Portuguese Language Teachers and Teaching of Textual Production in the Context of Basic, Technical and Technological Education" is included in the research line Teaching Training for Vocational and Technological Education, of the Master in Professional Education and Technological. The research was developed based on the question of how the Permanent Formation for Portuguese Language Teachers occurs and to what extent this training contributes to the teaching activity directed to the teaching of textual production at the Farroupilha Federal Institute, Júlio de Castilhos Campus. Based on this question, we sought to investigate the way in which the institution enables the permanent formation of teachers, to identify the difficulties encountered by these teachers in the constant improvement of their teaching performance in what corresponds to the teaching of textual production, and to verify to what extent The permanent formations carried out by these teachers have contributed to the improvement of the teaching of textual production in courses of intermediate level integrated modality. The methodology of the research was based on the qualitative approach, with case study, and the subjects were the Portuguese Language teachers of the IFFar - Júlio de Castilhos Campus who teach classes in the Agricultural Technical and Computer Technician course. The data made it possible to understand the way in which this process of permanent training of Portuguese Language teachers, focused on teaching textual production, contributed to qualify teaching in integrated courses in the Institution.